Pengaruh Suku Bunga BI dan Inflasi Terhadap Kinerja (ROA) Bank Umum Syari'ah - Muhammad Fakhri Imaduddin; Nursito Nursito (Journal of Economic, Bussines and Accounting (COSTING), 2023)
This study aimed to determine The Effect of BI Interest Rate and Inflation on Perfomance by Return On Assets (ROA). The population of this study is Syari’ah Banking Company listed on the Financial Services Authority (OJK) Period 2017-2019. The sampling technique is done by purposive sampling so Syari’ah Banking Company listed on the Financial Services Authority (OJK) Period 2017-2019 are samples. Data analysis technique used descriptive statistics, clasic assumption test, and hypothesis testing with multiple linear regression. The result of this study indicated that BI Interest Rate and Inflation has no effect and on Performance (ROA). The result of this study indicated that partially BI Interest Rate has no effect on Performance (ROA), and Inflation has no effect on Performance (ROA). Keywords: BI Interest Rate, Inflation, ROA